If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -2) + (x + 1) + x + (x + 1) = x + (2x + -9) + (x + 1) + (x + 8) + x Reorder the terms: (-2 + 2x) + (x + 1) + x + (x + 1) = x + (2x + -9) + (x + 1) + (x + 8) + x Remove parenthesis around (-2 + 2x) -2 + 2x + (x + 1) + x + (x + 1) = x + (2x + -9) + (x + 1) + (x + 8) + x Reorder the terms: -2 + 2x + (1 + x) + x + (x + 1) = x + (2x + -9) + (x + 1) + (x + 8) + x Remove parenthesis around (1 + x) -2 + 2x + 1 + x + x + (x + 1) = x + (2x + -9) + (x + 1) + (x + 8) + x Reorder the terms: -2 + 2x + 1 + x + x + (1 + x) = x + (2x + -9) + (x + 1) + (x + 8) + x Remove parenthesis around (1 + x) -2 + 2x + 1 + x + x + 1 + x = x + (2x + -9) + (x + 1) + (x + 8) + x Reorder the terms: -2 + 1 + 1 + 2x + x + x + x = x + (2x + -9) + (x + 1) + (x + 8) + x Combine like terms: -2 + 1 = -1 -1 + 1 + 2x + x + x + x = x + (2x + -9) + (x + 1) + (x + 8) + x Combine like terms: -1 + 1 = 0 0 + 2x + x + x + x = x + (2x + -9) + (x + 1) + (x + 8) + x 2x + x + x + x = x + (2x + -9) + (x + 1) + (x + 8) + x Combine like terms: 2x + x = 3x 3x + x + x = x + (2x + -9) + (x + 1) + (x + 8) + x Combine like terms: 3x + x = 4x 4x + x = x + (2x + -9) + (x + 1) + (x + 8) + x Combine like terms: 4x + x = 5x 5x = x + (2x + -9) + (x + 1) + (x + 8) + x Reorder the terms: 5x = x + (-9 + 2x) + (x + 1) + (x + 8) + x Remove parenthesis around (-9 + 2x) 5x = x + -9 + 2x + (x + 1) + (x + 8) + x Reorder the terms: 5x = x + -9 + 2x + (1 + x) + (x + 8) + x Remove parenthesis around (1 + x) 5x = x + -9 + 2x + 1 + x + (x + 8) + x Reorder the terms: 5x = x + -9 + 2x + 1 + x + (8 + x) + x Remove parenthesis around (8 + x) 5x = x + -9 + 2x + 1 + x + 8 + x + x Reorder the terms: 5x = -9 + 1 + 8 + x + 2x + x + x + x Combine like terms: -9 + 1 = -8 5x = -8 + 8 + x + 2x + x + x + x Combine like terms: -8 + 8 = 0 5x = 0 + x + 2x + x + x + x 5x = x + 2x + x + x + x Combine like terms: x + 2x = 3x 5x = 3x + x + x + x Combine like terms: 3x + x = 4x 5x = 4x + x + x Combine like terms: 4x + x = 5x 5x = 5x + x Combine like terms: 5x + x = 6x 5x = 6x Solving 5x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5x + -6x = 6x + -6x Combine like terms: 5x + -6x = -1x -1x = 6x + -6x Combine like terms: 6x + -6x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| P=4L+3w | | 10(z-4)=(12)z/2 | | 9pq^4-9pr^4=0 | | 2h^2-11h-40= | | 3x/6x^3 | | -(4x-2y-2)= | | 0=8d^2-26d-15 | | 2(m+4)-3m=14 | | (X+8)=29 | | log[5](2x^6)=0 | | z/5-5=7/6 | | -50=-6x-5(-2x+18) | | x/12-3=11/24 | | 8+3x=2x-9 | | 2x^3+21x^2=40x | | 180=x+6.2x | | 3x+8=2y+x | | 6x-x=-2-3 | | 16+1x=-5x+8 | | .5x+2=-3y | | y=8+12 | | 2-3/10=10 | | 25p^2-70p+49=0 | | (5x+6)(4x+6)= | | (3p5m-2)/(18pm5) | | 7x-2x+x=6x | | 5.3-2.8x= | | y=-28-24 | | 2=r/3-3 | | 8(-21x+26)=49(-46+9x) | | 8x-x=-2-3 | | -3(x+4)=5x-10 |